Employee Spinouts, Social Networks, and Family Firms - James E. Rauch (Center for Economic Studies and ifo Institute (CESifo), 2013)
Recently collected data show that, within any manufacturing industry, vertically integrated firms tend to have larger, higher productivity plants, account for the bulk of sales, and also sell externally most of the inputs they produce. In a weak contracting environment characteristic of developing countries, vertically integrated firms are vulnerable to employee spinouts: managers of input divisions can start their own firms, making customized inputs formerly provided internally subject to hold-up and capturing the profits formerly made from external sales of generic inputs. This vulnerability is shown to lead to inefficiently low entry. Vertically integrated firms can fight back by hiring managers for their input divisions who are members of networks that informally sanction hold-ups or children who keep profits in the family even if they spin out. This is shown to predict the association of co-ethnic networks with high rates of entrepreneurship and the prominence of family-owned business groups in developing country manufacturing.
Keywords: L14; L22; L26; 330; employee spinouts; social networks; family firms; vertical disintegration; entrepreneurship; business groups